Sensitivity Analysis of Acoustic Parameters in a Theatre Hall: A Case Study of the Maria Zankovetska Theatre in Lviv - RUBACHA, Jarosław; PILCH, Adam; KINASZ, Roman; BINEK, Wojciech; KAMISIŃSKI, Tadeusz; MELNYK, Mykhaylo (Archives of Acoustics, 2025)
This article explores the potential for modifying acoustic parameters within a theatre hall, using the Maria Zankovetska Theatre in Lviv, as a case study. The study used sensitivity analysis to evaluate how changes in the sound absorption of specific surfaces affect selected acoustic parameters in the horseshoe-shaped theatre hall. A numerical model of the hall is developed and calibrated based on in-situ acoustic measurements to assess the sensitivity of parameters such as reverberation time (T20), early decay time (EDT), clarity (C50), and early sound strength (G80). The analysis reveals that surfaces such as the stage tower ceiling, stage walls with curtains, audience walls, and seating have the most significant impact on the acoustic parameters. Modifying the sound absorption of these surfaces can affect T20, EDT, C50, and G80. Notably, increasing the absorption of a single surface might not significantly alter C50 and G80 values, whereas reducing the absorption of surfaces such as seating can lead to noticeable changes in these parameters. These findings provide valuable insights for future renovations and acoustic adjustments, aiming to optimize the theatre’s acoustic performance while preserving its historical character.